The Resolution of Ojek Online Vs. Traditional Public Transportation Conflict - Ikeu Kania; Dini Turipanam Alamanda; Mila Karmila; Ahmad Kurniawan (Indonesian Association for Public Administration (IAPA), 2020)
Nowadays, the demand for people mobility is getting higher. The breakthrough of online application-based transportation innovation such as Go-Jek combining transportation with communication technology through smartphone requires the people to decide which transportation is most compatible to their need. The presence of something innovative in many areas can get resistance, so can the presence of ojek online (online taxibike) in Garut Regency getting resistance from conventional transportation, particularly ojek pangkalan (base taxibike) and city public transportation (angkot) ending up with conflict. This research aims to provide an alternative solution by means of organizing conflict mapping, conflict resolution process, and conflict resolution. Research method employed was qualitative approach, while data was obtained through observation and interview with 8 informants. The result of research showed that factors becoming the main source of conflict are social factor related to the passenger preferring ojek online, ojek online picking up passenger in ojek pangkalan and city public transportation areas and economic factor including cheaper tariff of ojek online.